1973
DOI: 10.3758/bf03326915
|View full text |Cite
|
Sign up to set email alerts
|

The effects of dorsal hippocampal lesions on reinforcement shifts

Abstract: This experiment attempted to clarify the effects of dorsal hippocampal lesions on a lick-rate response to reinforcement shifts. Rats received preshift solutions of either 4% or 32% sucrose and were then shifted to the opposite concentration. The results indicated (1) that Ss shifted to the increased concentration quickly adjusted to the control levels. and (2) a negative contrast effect (NCE) for both hippocampal and sham downshift groups. These results are in contrast to earlier fail!lres to find a NCE in hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

1974
1974
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 10 publications
3
10
0
Order By: Relevance
“…It has been shown that reward thresholds are lower during the presentation of an ascending current series, in comparison to random or descending current series [12,28]. Rats with hippocampal lesions have previously been described as being 'extremely sensitive' to contrast effects engendered by shifts in reward [31], and it has recently been reported that rats with extensive hippocampal damage were more sensitive than controls to 'increases' in the qualitative aspects of reward [48]. The current results confirm these earlier observations, and, in the case of ICSS, suggest that lesioned animals may be more sensitive to positive, rather than negative, contrasts.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that reward thresholds are lower during the presentation of an ascending current series, in comparison to random or descending current series [12,28]. Rats with hippocampal lesions have previously been described as being 'extremely sensitive' to contrast effects engendered by shifts in reward [31], and it has recently been reported that rats with extensive hippocampal damage were more sensitive than controls to 'increases' in the qualitative aspects of reward [48]. The current results confirm these earlier observations, and, in the case of ICSS, suggest that lesioned animals may be more sensitive to positive, rather than negative, contrasts.…”
Section: Discussionmentioning
confidence: 99%
“…Contrast effects have been reported in another paradigm. The effects of aspiration lesions (Murphy & Brown, 1970) or radio-frequency lesions (Kramarcy, Mikulka, & Freeman, 1973) of the dorsal hippocampus on lick-rate response to reinforcement shifts have been investigated. Food deprived, lesioned animals in both experiments exhibited rapid decreases in licking when sucrose solution was changed from 32% to 4%.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of hippocampal lesions on contrast in consummatory behavior are not clear. One study found that hippocampal lesions had no effect on the negative contrast that occurs when rats are shifted from 32% to 4% sucrose (Kramarcy, Mikulka, & Freeman, 1973), but another study with a nearly identical procedure found that such lesions prevented the occurrence of negative contrast (Murphy & Brown, 1970). There were differences in the size of the lesions reported in these studies, small lesions restricted to the dorsal hippocampus in the Kramarcy et al experiment and larger lesions in the Murphy and Brown experiment, but there was still some sparing of the ventral tips of the hippocampus in the latter study.…”
Section: Methodsmentioning
confidence: 99%